Better be a good sermon : preaching for special occasions and contexts - Weller, Keith, ed.; Lane, Adrian, ed. (Australia : Acorn Press, 2011)
Preachers often face the prospect of preaching at a variety of occasions that can be deemed 'special' in some way, perhaps because of the occasion itself or the make-up of the particular audience. The regular Christian festivals of Christmas, Easter and Pentecost are examples of these, as are the pastoral services of baptism, weddings and funerals that arise irregularly, sometimes frequently and with little warning. Then there are the 'one-off' special occasions such as a time of national tragedy or an Annual General Meeting of an organisation. Each occasion has its particular challenges and the preacher must be attuned to the subtleties that need to be attended to in each.Audiences may be in rural, school, multicultural or secular settings with varying demographics such as age, socio-economic status and ethnicity. And especially on these occasions, preachers' words and their lives are very much open to public scrutiny. Therefore how preachers live out their everyday lives in their communities will also deliver a powerful sermon to those who watch and listen.The Simeon Association Inc. was encouraged to consider preparing a second book on preaching by the positive response it has received from the first, Please! No More Boring Sermons. The Association has again sought out well-credentialed clergy and lay people to provide examples of sermons preached in a wide range of situations that will be of immense assistance to all who find themselves given the responsibility of preaching on special occasions. Following the format of the first book, well-credentialed preachers were invited to contribute a chapter and/or sermon pertinent to special occasions. The sermons were not prepared especially for the book, but were preached on real occasions to real congregations or audiences without thought for possible publication. The date and place of original presentation is recorded for each sermon.
Keywords: Preaching; Sermons; Festival day sermons